A series of d10 coordination polymers constructed with a rigid tripodal imidazole ligand and varied polycarboxylates: syntheses, structures and luminescence properties1. Issue 9 (7th March 2015) - Xue, Zhenzhen; Sheng, Tianlu; Wang, Yanlong; Hu, Shengmin; Wen, Yuehong; Wang, Yong; Li, Haoran; Fu, Ruibiao; Wu, Xintao
<x xml:space="preserve">Abstract</x> Five novel Zn(ii)/Cd(ii) coordination polymers have been synthesized under solvothermal conditions.